Single dose versus multiple doses of antibiotics in women undergoing caesarean section: a randomized non-inferiority trial - Agarwal, Krishna; Lamba, Hansveen Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study aimed to compare the rates of surgical site infection in women undergoing caesarean section, given either a single dose of antibiotic 30-60 minutes before giving skin incision or multiple doses. There is enough evidence available from high-income countries supporting a single dose of prophylactic antibiotic. However, there is scanty data from middle- and low-income countries. Methods: An open-ended randomized trial was undertaken on 400 women undergoing caesarean section. Women in the intervention group were given one dose of intravenous cefazolin before skin incision. Women in the comparison group were given intravenous ceftriaxone before skin incision, and intravenous ceftriaxone plus metronidazole for forty-eight hours after caesarean. Results: There was no significant difference between the single and multiple-dose regimen of antibiotic prophylaxis in caesarean sections when compared for postoperative surgical site infections. Secondary outcome variables, that is, side-effects of antibiotics were significantly more in the multiple-dose group. Conclusions: A single-dose regimen for antibiotic prophylaxis is as effective as a multiple-dose regimen, in low-risk women undergoing caesarean section, both elective and emergency.